'They only smoke in the house when I'm not in': understanding the limited effectiveness of a smoke-free homes intervention. (23rd April 2020) - O'Donnell, R; Amos, A; Turner, S W; Adams, L; Henderson, T; Lyttle, S; Mitchell, S; Semple, S
Abstract: Background: Children's second-hand smoke (SHS) exposure in the home is highest in socio-economically disadvantaged areas. Personalized household air-quality measurements can promote changes in smoking that reduce SHS exposure. The 'First Steps 2 Smoke-free' (FS2SF) intervention is the first to trial this approach delivered as part of health professionals' routine work. This paper reports the findings of qualitative interviews with participants that explored their experiences of the intervention and why outcomes varied. Methods: 120 women were recruited from the NHS First Steps Programme, which supports disadvantaged mothers. They received either personalized feedback on their home air quality and advice on reducing SHS or standard SHS advice. Qualitative interviews with 15 mothers were analyzed thematically using the Capability, Opportunity, Motivation, Behaviour (COM-B) model. Results: The intervention increased women's capability to change home-smoking behaviour, through increasing awareness and salience of SHS risks to their children, and motivation to act. However, taking effective action was constrained by their limited social and environmental opportunities, including others' smoking in the home. Conclusions: The FS2SF intervention was ineffective as it was unable to fully address the precarious, complex life circumstances that make creating a smoke-free home particularly difficult for women experiencing intersecting dimensions of disadvantage.